2013
DOI: 10.1111/nep.12036
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes in community‐acquired versus hospital‐acquired acute kidney injury

Abstract: We conclude that CA-AKI is a common cause of AKI that is as severe as that seen in HA-AKI. CA-AKI has a significant impact on length of hospital stay, mortality, and the development and/or progression of chronic kidney disease. Strategies to limit the risk of CA-AKI are likely to have a significant impact on healthcare costs and patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
89
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 26 publications
10
89
1
2
Order By: Relevance
“…We compared this cohort with 334 patients who sustained AKI during a hospital stay. The incidence of CA-AKI was higher in the present study than in other studies (9,(20)(21)(22)(23). However, this probably remains an underestimate of the true amount of CA-AKI that exists because numerous patients with CA-AKI will neither have blood tests performed nor be admitted to the hospital.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…We compared this cohort with 334 patients who sustained AKI during a hospital stay. The incidence of CA-AKI was higher in the present study than in other studies (9,(20)(21)(22)(23). However, this probably remains an underestimate of the true amount of CA-AKI that exists because numerous patients with CA-AKI will neither have blood tests performed nor be admitted to the hospital.…”
Section: Discussioncontrasting
confidence: 54%
“…AKI is an important contributor to CKD. Previous studies have highlighted increased risks of de novo CKD following episodes of AKI with incomplete recovery (3,15,16,22,25). In this study, one third of patients developed de novo CKD or progression of preexisting CKD.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…At present, it is essential to develop health care aimed at prevention in order to mitigate the risks of disease chronification, the worsening of chronic diseases, the onset of new cases and comorbidities. Studies report the frequent onset of AKI primarily in the community by considering that many hospitalized patients present elevated serum creatinine since the time of admission, foretelling a previous history of the disease (13)(14)(15) . The care of individuals with AKI should be a priority regardless of where they are located for promoting their safety (2,16) .…”
Section: Introductionmentioning
confidence: 99%
“…Our observation match with that of Schissler et al who observed respiratory disease in 39.6% of admitted patients. 16 Singh et al in India observed similar frequency of hepatobiliary diseases (25.49%), infections (21.57%) and diabetes (3.92%). 17 AKI was observed in 104 (27.2%) patients in our settings.…”
Section: Discussionmentioning
confidence: 70%